Varietal Influence on the Abundance and Community Structure of Plant-Parasitic Nematodes in Potato Fields of Solok Regency, Indonesia - Tama, Duma Putri; Trizelia; Liswarni, Yenny; Ananda, Hal Adi Fikri; Hidayatullah, Annisa (Jurnal Research Ilmu Pertanian, 2026)
Potatoes (Solanum tuberosum L.) are a strategic horticultural commodity in Indonesia, but their productivity is often hampered by attacks from plant-parasitic nematodes. This study aims to determine the effect of potato varieties on the abundance and structure of plant-parasitic nematode communities in the potato production centre of Solok Regency. Soil samples were collected randomly using the zig-zag method from red and white potato fields at several locations with different elevations. Nematodes were extracted using the Baermann funnel method, followed by population calculation, genus identification, and frequency of occurrence analysis. The results showed that the parasitic nematode community was dominated by the genus Meloidogyne in both varieties, with higher populations and frequency of occurrence in red potato varieties. White potato varieties showed lower total nematode populations with more diverse community structures. These differences indicate the influence of variety on the development of plant parasitic nematode populations. These findings emphasise the importance of variety selection as part of an integrated nematode management strategy in potato cultivation in Solok Regency.